Lipids and high-value astaxanthin produced in a cupboard by heterotrophic Chromochloris zofingiensis: Improvement of process efficiency - Cakir, Zeynep Busra; Özkan, Melek (Elsevier, 2023)
Cultivation of microalgae with high lipid content continues to be pursued as a potential biodiesel feedstock. Processing of microalgae biomass is not sufficiently cost-efficient to allow for wide-scale implementation. Efficient, low-cost processing strategies must be developed. In this study, heterotrophic metabolism was combined with attached cultivation for co-production of lipids and astaxanthin to simplify processing, improve efficiency, and mitigate cost. Microalgae were cultivated on agar media surface so that culture was distributed homogeneously with high solid content (40 %) and harvesting was possible with little manual effort. Operational parameters - initial glucose, inoculation ratio, cultivation time and temperature, and dry vs. wet extraction - were tested and optimized to maximize lipid production. Accordingly, room temperature incubation for 30 days in a dark cupboard with 40 g/L initial glucose, 4 % inoculum, and wet extraction of the harvested biomass yielded 8.2 g/L lipids and 6.5 mg/L astaxanthin. Many advantages are observed with agar-attached cultivation of microalgae, including no energy input required to support the incubation term, simple and manual harvesting of cells, and no dewatering or drying needed for the extraction of biomass. Based on the benefits when compared to traditional suspended or attached cultivation, agar-attached growth for lipids and astaxanthin co-production has the potential to greatly improve the process efficiency and thus, feasibility, of using microalgae as an alternative fuel source.
Keywords: Microalgae; Lipids; Astaxanthin; Heterotrophic; Attached cultivation